Mechanical Properties and Microstructure Characteristics of the Loess Modified by the Consolid System - Yongde Liu; Yongdong Yang; Yunxiu Dong; Yuanfang Lv; Dong Wang; Lei Qi (Advances in Materials Science and Engineering)
The soil stabilizer of the Consolid system (content: 0%–2.46%) was used for the modification of collapsible loess. The consolidation test, compression test, collapsibility test, and strength test of modified loess were conducted. In addition, X-ray diffraction (XRD), scanning electron microscopy (SEM), and mercury injection tests were carried out to study the loess before and after modification. The results indicated that with an increase in the content of the stabilizers, the optimal water content of the modified loess increased, whereas the dry density decreased. Furthermore, as the content of the stabilizers increased, the compressibility and collapsibility of the modified loess decreased. When the stabilizer content was 0.86%, the modified loess exhibited almost no collapsibility. The unconfined compressive strength of the modified loess demonstrated an exponential relationship with the content of the stabilizers. The shear strength increased with the increase in the content of the stabilizers. When the stabilizer content reached 1.66%, the friction angle started to decrease. The microstructure analysis indicated that the cumulative pore volume of the modified loess decreased with the increase in the content of the stabilizers, which could facilitate the formation of a more stable soil structure and improve the impermeability and strength.